Leading-edge tubercles as an alternative to increasing a Francis turbine torque generation - Campos, Henrique M. [UNESP]; Salviano, Leandro O. [UNESP]; Pantaleão, Aluisio V. [UNESP] (Elsevier, 2024)
Hydroelectricity accounts for 63.8% of Brazilian electricity, but several of the country's power plants require modernization. For this, the insertion of leading-edge tubercles is an alternative since this device improves wind and tidal turbines. Surprisingly, no study explored the device's potential for hydraulic turbine improvement. To address this gap, numerical simulations were conducted in Ansys CFX to assess the tubercles’ effects on the performance of Francis turbines. For this, the current study validated the simulations and tested the impacts of the tubercle structural parameters variation over the benchmarking turbine Francis-99 and applied the device in a non-modernized runner blade to evaluate its effects on equipment performance. The parameters test revealed that variations in tubercle amplitude and waviness ratio improved the torque generation up to 0.34% despite elevating the net head up to 0.43%. In the non-modernized blade, the device increased the torque generation and net head up to 1.77% and 4.13%, respectively, proving that the tubercles are an alternative for hydraulic turbine improvement. Also, the flow field analysis exhibits that the device creates vortices that influence the blade pressure side, delaying boundary layer detachment, agreeing with other results in the literature.
Keywords: Bio-inspired devices; Francis turbines; Francis-99; Leading-edge tubercles; Passive flow control methods